Implementasi Kebijakan Pengembangan Profesionalisme Aparatur Birokrasi Dalam meningkatkan Prestasi Kerja di Biro Organisasi Sekretariat Daerah Propinsi Sulawesi Utara - Lakada, Sintya Nanda (Sam Ratulangi University, 2013)
Abstract : From the results of research conducted by the researchers , that Impementasi Professional Development Policy Reform Improve Job Performance Bureaucracy In Organization Bureau Secretariat in North Sulawesi . Results of linear regression and simple correlation analysis turns Impementasi Professional Development Policy Reform and relationships have a positive effect on Job Performance in Organizations Secretariat Bureau of North Sulawesi . This research can be classified as an explorative survey research with quantitative methods approach . Based on the results of the study suggested professional development policy should be able to optimize the bureaucratic apparatus of education and training in the form of structurally training , functional training , technical training and professional development of personnel policy implementation Yag needs greater attention is the education and training ( technical and functional training ) because this training proved very effective for developing professionalism bureaucratic apparatus in order to optimize the execution of job duties professional development of personnel policy implementation the budget allocation for education and in-service training should be improved . This is necessary because the transactions are carried out based on information obtained through this research budget allocated pengembanga bureaucratic apparatus professionalism through education and training is still small .Keywords : Implementation, Policy, Professionalism, Bureaucracy, Job Performance